MAYBE Initial complexity problem: 1: T: (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) (1, 1) f0(a, b, c) -> f2(a, b, c) [ a >= 0 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a, b, c) [ a >= 0 ] with all transitions in problem 1, the following new transitions are obtained: f0(a, b, c) -> f2(a + c, b, c - 2) [ a >= 0 ] f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] We thus obtain the following problem: 2: T: (1, 2) f0(a, b, c) -> f2(a + c, b, c - 2) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + c, b, c - 2) [ a >= 0 ] with all transitions in problem 2, the following new transitions are obtained: f0(a, b, c) -> f2(a + 2*c - 2, b, c - 4) [ a >= 0 ] f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] We thus obtain the following problem: 3: T: (1, 3) f0(a, b, c) -> f2(a + 2*c - 2, b, c - 4) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 2*c - 2, b, c - 4) [ a >= 0 ] with all transitions in problem 3, the following new transitions are obtained: f0(a, b, c) -> f2(a + 3*c - 6, b, c - 6) [ a >= 0 ] f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] We thus obtain the following problem: 4: T: (1, 4) f0(a, b, c) -> f2(a + 3*c - 6, b, c - 6) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 3*c - 6, b, c - 6) [ a >= 0 ] with all transitions in problem 4, the following new transitions are obtained: f0(a, b, c) -> f2(a + 4*c - 12, b, c - 8) [ a >= 0 ] f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] We thus obtain the following problem: 5: T: (1, 5) f0(a, b, c) -> f2(a + 4*c - 12, b, c - 8) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 4*c - 12, b, c - 8) [ a >= 0 ] with all transitions in problem 5, the following new transitions are obtained: f0(a, b, c) -> f2(a + 5*c - 20, b, c - 10) [ a >= 0 ] f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] We thus obtain the following problem: 6: T: (1, 6) f0(a, b, c) -> f2(a + 5*c - 20, b, c - 10) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 5*c - 20, b, c - 10) [ a >= 0 ] with all transitions in problem 6, the following new transitions are obtained: f0(a, b, c) -> f2(a + 6*c - 30, b, c - 12) [ a >= 0 ] f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] We thus obtain the following problem: 7: T: (1, 7) f0(a, b, c) -> f2(a + 6*c - 30, b, c - 12) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 6*c - 30, b, c - 12) [ a >= 0 ] with all transitions in problem 7, the following new transitions are obtained: f0(a, b, c) -> f2(a + 7*c - 42, b, c - 14) [ a >= 0 ] f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] We thus obtain the following problem: 8: T: (1, 8) f0(a, b, c) -> f2(a + 7*c - 42, b, c - 14) [ a >= 0 ] (1, 8) f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 7*c - 42, b, c - 14) [ a >= 0 ] with all transitions in problem 8, the following new transitions are obtained: f0(a, b, c) -> f2(a + 8*c - 56, b, c - 16) [ a >= 0 ] f0(a, b, c) -> f2(a + 7*c + b - 42, b - 2, c - 13) [ a >= 0 ] We thus obtain the following problem: 9: T: (1, 9) f0(a, b, c) -> f2(a + 8*c - 56, b, c - 16) [ a >= 0 ] (1, 9) f0(a, b, c) -> f2(a + 7*c + b - 42, b - 2, c - 13) [ a >= 0 ] (1, 8) f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 8*c - 56, b, c - 16) [ a >= 0 ] with all transitions in problem 9, the following new transitions are obtained: f0(a, b, c) -> f2(a + 9*c - 72, b, c - 18) [ a >= 0 ] f0(a, b, c) -> f2(a + 8*c + b - 56, b - 2, c - 15) [ a >= 0 ] We thus obtain the following problem: 10: T: (1, 10) f0(a, b, c) -> f2(a + 9*c - 72, b, c - 18) [ a >= 0 ] (1, 10) f0(a, b, c) -> f2(a + 8*c + b - 56, b - 2, c - 15) [ a >= 0 ] (1, 9) f0(a, b, c) -> f2(a + 7*c + b - 42, b - 2, c - 13) [ a >= 0 ] (1, 8) f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 9*c - 72, b, c - 18) [ a >= 0 ] with all transitions in problem 10, the following new transitions are obtained: f0(a, b, c) -> f2(a + 10*c - 90, b, c - 20) [ a >= 0 ] f0(a, b, c) -> f2(a + 9*c + b - 72, b - 2, c - 17) [ a >= 0 ] We thus obtain the following problem: 11: T: (1, 11) f0(a, b, c) -> f2(a + 10*c - 90, b, c - 20) [ a >= 0 ] (1, 11) f0(a, b, c) -> f2(a + 9*c + b - 72, b - 2, c - 17) [ a >= 0 ] (1, 10) f0(a, b, c) -> f2(a + 8*c + b - 56, b - 2, c - 15) [ a >= 0 ] (1, 9) f0(a, b, c) -> f2(a + 7*c + b - 42, b - 2, c - 13) [ a >= 0 ] (1, 8) f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 10*c - 90, b, c - 20) [ a >= 0 ] with all transitions in problem 11, the following new transitions are obtained: f0(a, b, c) -> f2(a + 11*c - 110, b, c - 22) [ a >= 0 ] f0(a, b, c) -> f2(a + 10*c + b - 90, b - 2, c - 19) [ a >= 0 ] We thus obtain the following problem: 12: T: (1, 12) f0(a, b, c) -> f2(a + 11*c - 110, b, c - 22) [ a >= 0 ] (1, 12) f0(a, b, c) -> f2(a + 10*c + b - 90, b - 2, c - 19) [ a >= 0 ] (1, 11) f0(a, b, c) -> f2(a + 9*c + b - 72, b - 2, c - 17) [ a >= 0 ] (1, 10) f0(a, b, c) -> f2(a + 8*c + b - 56, b - 2, c - 15) [ a >= 0 ] (1, 9) f0(a, b, c) -> f2(a + 7*c + b - 42, b - 2, c - 13) [ a >= 0 ] (1, 8) f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 11*c - 110, b, c - 22) [ a >= 0 ] with all transitions in problem 12, the following new transitions are obtained: f0(a, b, c) -> f2(a + 12*c - 132, b, c - 24) [ a >= 0 ] f0(a, b, c) -> f2(a + 11*c + b - 110, b - 2, c - 21) [ a >= 0 ] We thus obtain the following problem: 13: T: (1, 13) f0(a, b, c) -> f2(a + 12*c - 132, b, c - 24) [ a >= 0 ] (1, 13) f0(a, b, c) -> f2(a + 11*c + b - 110, b - 2, c - 21) [ a >= 0 ] (1, 12) f0(a, b, c) -> f2(a + 10*c + b - 90, b - 2, c - 19) [ a >= 0 ] (1, 11) f0(a, b, c) -> f2(a + 9*c + b - 72, b - 2, c - 17) [ a >= 0 ] (1, 10) f0(a, b, c) -> f2(a + 8*c + b - 56, b - 2, c - 15) [ a >= 0 ] (1, 9) f0(a, b, c) -> f2(a + 7*c + b - 42, b - 2, c - 13) [ a >= 0 ] (1, 8) f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 12*c - 132, b, c - 24) [ a >= 0 ] with all transitions in problem 13, the following new transitions are obtained: f0(a, b, c) -> f2(a + 13*c - 156, b, c - 26) [ a >= 0 ] f0(a, b, c) -> f2(a + 12*c + b - 132, b - 2, c - 23) [ a >= 0 ] We thus obtain the following problem: 14: T: (1, 14) f0(a, b, c) -> f2(a + 13*c - 156, b, c - 26) [ a >= 0 ] (1, 14) f0(a, b, c) -> f2(a + 12*c + b - 132, b - 2, c - 23) [ a >= 0 ] (1, 13) f0(a, b, c) -> f2(a + 11*c + b - 110, b - 2, c - 21) [ a >= 0 ] (1, 12) f0(a, b, c) -> f2(a + 10*c + b - 90, b - 2, c - 19) [ a >= 0 ] (1, 11) f0(a, b, c) -> f2(a + 9*c + b - 72, b - 2, c - 17) [ a >= 0 ] (1, 10) f0(a, b, c) -> f2(a + 8*c + b - 56, b - 2, c - 15) [ a >= 0 ] (1, 9) f0(a, b, c) -> f2(a + 7*c + b - 42, b - 2, c - 13) [ a >= 0 ] (1, 8) f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 13*c - 156, b, c - 26) [ a >= 0 ] with all transitions in problem 14, the following new transitions are obtained: f0(a, b, c) -> f2(a + 14*c - 182, b, c - 28) [ a >= 0 ] f0(a, b, c) -> f2(a + 13*c + b - 156, b - 2, c - 25) [ a >= 0 ] We thus obtain the following problem: 15: T: (1, 15) f0(a, b, c) -> f2(a + 14*c - 182, b, c - 28) [ a >= 0 ] (1, 15) f0(a, b, c) -> f2(a + 13*c + b - 156, b - 2, c - 25) [ a >= 0 ] (1, 14) f0(a, b, c) -> f2(a + 12*c + b - 132, b - 2, c - 23) [ a >= 0 ] (1, 13) f0(a, b, c) -> f2(a + 11*c + b - 110, b - 2, c - 21) [ a >= 0 ] (1, 12) f0(a, b, c) -> f2(a + 10*c + b - 90, b - 2, c - 19) [ a >= 0 ] (1, 11) f0(a, b, c) -> f2(a + 9*c + b - 72, b - 2, c - 17) [ a >= 0 ] (1, 10) f0(a, b, c) -> f2(a + 8*c + b - 56, b - 2, c - 15) [ a >= 0 ] (1, 9) f0(a, b, c) -> f2(a + 7*c + b - 42, b - 2, c - 13) [ a >= 0 ] (1, 8) f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 By chaining the transition f0(a, b, c) -> f2(a + 14*c - 182, b, c - 28) [ a >= 0 ] with all transitions in problem 15, the following new transitions are obtained: f0(a, b, c) -> f2(a + 15*c - 210, b, c - 30) [ a >= 0 ] f0(a, b, c) -> f2(a + 14*c + b - 182, b - 2, c - 27) [ a >= 0 ] We thus obtain the following problem: 16: T: (1, 16) f0(a, b, c) -> f2(a + 15*c - 210, b, c - 30) [ a >= 0 ] (1, 16) f0(a, b, c) -> f2(a + 14*c + b - 182, b - 2, c - 27) [ a >= 0 ] (1, 15) f0(a, b, c) -> f2(a + 13*c + b - 156, b - 2, c - 25) [ a >= 0 ] (1, 14) f0(a, b, c) -> f2(a + 12*c + b - 132, b - 2, c - 23) [ a >= 0 ] (1, 13) f0(a, b, c) -> f2(a + 11*c + b - 110, b - 2, c - 21) [ a >= 0 ] (1, 12) f0(a, b, c) -> f2(a + 10*c + b - 90, b - 2, c - 19) [ a >= 0 ] (1, 11) f0(a, b, c) -> f2(a + 9*c + b - 72, b - 2, c - 17) [ a >= 0 ] (1, 10) f0(a, b, c) -> f2(a + 8*c + b - 56, b - 2, c - 15) [ a >= 0 ] (1, 9) f0(a, b, c) -> f2(a + 7*c + b - 42, b - 2, c - 13) [ a >= 0 ] (1, 8) f0(a, b, c) -> f2(a + 6*c + b - 30, b - 2, c - 11) [ a >= 0 ] (1, 7) f0(a, b, c) -> f2(a + 5*c + b - 20, b - 2, c - 9) [ a >= 0 ] (1, 6) f0(a, b, c) -> f2(a + 4*c + b - 12, b - 2, c - 7) [ a >= 0 ] (1, 5) f0(a, b, c) -> f2(a + 3*c + b - 6, b - 2, c - 5) [ a >= 0 ] (1, 4) f0(a, b, c) -> f2(a + 2*c + b - 2, b - 2, c - 3) [ a >= 0 ] (1, 3) f0(a, b, c) -> f2(a + c + b, b - 2, c - 1) [ a >= 0 ] (1, 2) f0(a, b, c) -> f2(a + b, b - 2, c + 1) [ a >= 0 ] (?, 1) f2(a, b, c) -> f2(a + b, b - 2, c + 1) (?, 1) f2(a, b, c) -> f2(a + c, b, c - 2) start location: f0 leaf cost: 0 Complexity upper bound ? Time: 5.870 sec (SMT: 5.615 sec)